(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
This is one of a series of articles building a map of elementary waves, based on experimental data and quantum mathematics. Previous articles showed that elementary waves carry no energy. Particles follow them backwards. Why? Elementary rays consist of probability amplitudes, which influence particles because that is what probability amplitudes do. Elementary waves are that part of nature corresponding to quantum mathematics. Since these waves are the physical analogs of quantum equations, those equations provide a roadmap to the world of elementary waves: a map written in hieroglyphs. Quantum math is our Rosetta stone. The quantum world is far, far more similar to the world of everyday experience than quantum experts think. Waves are in a superposition. Particles are not. Wave function collapse does not occur when we measure something. It had occurred much earlier, when the object came into existence. This resolves insoluble problems that stumped John von Neumann. The smooth functioning of a Schrödinger equation abruptly collapses into one specific eigenstate when a gun is fired, not when the bullet hits the target. The bullet that caused World War I is an example. That bullet caused an abrupt collapse of the smooth probabilities of commerce and diplomacy.